PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA BENGKULU - Juliyanti, Belti; Onsardi, Onsardi (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
The backdrop of research is based on the importance of companies for achieving of organizational goals. These factors have affects on company performance, such as work discipline and motivation. This study aims to examine how the work discipline and motivation towards perfomance of employees at local water company of Bengkulu City. The respondents of this study were 67 employees of local water Company, which data collection techniques by using simple random sampling. For data collection techniques were through observation and questionnaires. While for data analysis techniques by examining its multiple linear regression analysis and hypothesis test. The results of this study indicated that there were coordination between discipline and motivation as shown from its multiple linear regression, Y = 4,451 + 0,510 X1 + 1,103 X2. This obtained there was the increase from its coefficient of determination or R Squard (R2) = 0.809 that is equal to 80, 9%, while its remaining 19.1%, was influenced by other variables, not in this study. Furthermore, work discipline and discipline simultaneously have a significant effect on performance of employees, with value (sig) 0,000<alpha 0.05. Similarly, work discipline and individual motivation partially have a significant effect on employees performance, its significant values (sig) for work discipline (X1) 0.003 <alpha 0.05, and work motivation variable (X2) was 0,000 <alpha 0.05.Â Keywords: work discipline, motivation, employee performance.